Production Efficiency of Oyster Mushroom MSMEs in East Java Province - Kus Irawan Prabowo; Yulia Herdianti; Siti Kalimah (Journal of Economics and Social Sciences (JESS), 2026)
The phenomenon and problems found in the field are that many experienced oyster mushroom farmers who have been in business for more than four years have experienced a decline in turnover or profits and have even stopped their businesses. This is due to several factors, and a solution or answer must be found so that people who cultivate oyster mushrooms in East Java Province can run their businesses and improve them. One solution is to improve production efficiency by utilizing information from the internet, such as research journals and e-books related to oyster mushroom production. The objectives of this study are 1) to determine the production efficiency of oyster mushroom MSMEs using the methods that have been implemented, 2) to implement production efficiency by replacing nutrients with better ones and production energy, and 3) to apply production efficiency by replacing production energy. The research method used was qualitative research with a PAR (Participatory Action Research) approach. The results of the study showed that the percentage increase in the economic value of the second production compared to the first production after several changes was 195.325%, while the percentage increase in the economic value of the third production was 308.848%. Therefore, it can be concluded that the third production has a very high economic value for the community engaged in oyster mushroom production in East Java Province.